Gestaltungskriterien für ein Folgeabkommen zum Kyoto-Protokoll: Eine ökonomische Analyse des globalen Klimaschutzes - Carolin Kleber (University of Freiburg, Department of International Economic Policy (iep), 2011)
– Latest findings of climate change research indicate that anthropogenic greenhouse gas emissions since the beginning of the industrial revolution have significantly contributed to the observed rise in global mean temperature. In addition, a further rise, with the potential passing of critical tipping points in the climate system, is projected if emissions are not reduced. The Kyoto Protocol regulates the emissions from most developed countries for the period from 2008 to 2012. However, since the treaty came into force, the concentration of greenhouse gases in the atmosphere has been growing continuously. For the time past 2012, a post-Kyoto agreement is indispensable in order to effectively control worldwide emissions and to slow global warming. This paper defines necessary criteria for the construction of such an agreement from an economic point of view. The three major elements that characterize an international climate treaty are the emissions reduction path, the contracting parties and the instruments for achieving the agreed-upon targets. This paper shows that global emission reductions should be determined via the use of an Integrated Assessment Model (IAM) to equalize marginal costs and benefits of mitigation. An examination of the effectiveness of sub-global treaties reveals that induced emission reductions could either be offset or even overcompensated by increases in other states through the channels of carbon leakage and the so-called green paradox. Therefore it is essential that a post-Kyoto agreement includes all or at least the most important global emitters. Although the well-known Weitzman theorem advocates the use of price-based rather than quantity-based instruments in climate policy, this paper recommends using an international cap-and-trade system. This market-based instrument overcomes implementation problems related to international taxes and is better suited to reach ecological effectiveness. Additional mechanisms for improving time flexibility can be used to avoid allowance price volatility and undesirable high compliance costs. A burden sharing rule that determines the allocation of emissions allowances among the contracting parties should be based on a polluter-pays- as well as an ability-to-pay-principle. This combination is likely to reveal a high level of acceptance among the negotiating states because it seems to be a reasonable application of the idea of the common, but differentiated responsibilities specified in the United Nations Framework Convention on Climate Change (UNFCCC). The paper concludes with the determination of enforcement strategies and a discussion of implementation problems. The definition of a less ambitious reduction target as well as the use of issue linkage could be helpful strategies to achieve a higher probability of international cooperation.
Keywords: 330; Klimaschutz; Umweltabgabe; Internationale Umweltpolitik; Emissionshandel; Welt